Térbeliség, társadalom és identitás összefüggései a XX. századi Szlovákiában - Murányi, Péter (Közép-Európai Közlemények, 2011)
The Slovak Republic is the youngest state in the Carpathian basin. Before World War I its territory was part of the Austro)Hungarian Empire. After the Peace Treaty of Trianon, it became part of the Czechoslovakian Republic which surely cannot be described as a ‘country of one)nation’. The new state had to accommodate many different minorities, including Germans and Hungarians, within its borders. After World War II, the majority of the largest minorities were relocated from the newly reformed country. Decades after sharing the same country with the Czechs, Slovakians finally decided to go their separate ways: In 1993 the Slovak Republic was born. The country, that shares borders with Hungary, has always tried to identify itself as the national state of Slovakians. Furthermore, none of its governments have adopted an adequate law on minorities to date. While forming its own administrative structure and territorial division in the 20th century, Slovakia fully ignored its long-standing natural borders in order to adapt to Slavic traditions with no consideration for old and ossified ones. This paper attempts to reveal the correlations between spatial processes, society and collective (national) identity with the intention to let researchers from different areas rethink the topic mentioned above.